Integrative Analysis of Transcriptomic and Metabolomic Profiles Uncovers the Mechanism of Color Variation in the Tea Plant Callus - Mengna Xiao; Yingju Tian; Ya Wang; Yunfang Guan; Ying Zhang; Yuan Zhang; Yanlan Tao; Zengquan Lan; Dexin Wang (Plants)
Tea plants (Camellia sinensis) are among the world’s most significant economic tree species. Tissue culture serves as a crucial method in commercial breeding by facilitating the rapid propagation of valuable genotypes and the generation of disease-free clones. However, callus browning represents a prevalent challenge in tea plant tissue culture, and may adversely affect explant growth and development. Our research demonstrates that although anti-browning agents can effectively suppress browning, they induce distinct color changes in the callus. These color variations could significantly influence callus induction and subsequent growth patterns. In this study, callus tissues from C. sinensis var. Assamica cv. Mengku were employed as experimental materials and treated with three commonly used anti-browning agents: ascorbic acid (VC), activated carbon (AC), and polyvinylpyrrolidone (PVP). The results demonstrated that while these three reagents effectively inhibited browning, they also induced distinct color changes in the explants, which appeared red, green, and white, respectively. Furthermore, this study investigated the molecular mechanisms underlying callus color changes using transcriptomic and metabolomic approaches. Based on transcriptome analysis, it was revealed that photosynthesis and flavonoid biosynthesis pathways were significantly enriched. Metabolome analysis identified 14 phenolic acids, which exhibited significant variation in accumulation across calluses of different colors. The differential expression of genes involved in flavonoid biosynthesis pathways, coupled with the distinct accumulation patterns of metabolites, can effectively alleviate photooxidative damage and enhance the resistance of callus to browning. AC activates the photosynthesis of callus by regulating carbon source allocation and upregulating the expression of key genes in the psa, psb, and pet families within the photosynthetic system. This process promotes chlorophyll biosynthesis, thereby enabling the callus to grow green, while VC activates the expression of key genes such as CHS, F3H, C4H, CYP75B1, and ANR in the flavonoid pathway, which are involved in the regulation of pigment synthesis in red callus. This study elucidated the molecular mechanisms underlying the effects of anti-browning agents on color variations in C. sinensis callus, thereby providing a robust theoretical foundation for optimization, the establishment of tea plant tissue culture systems, and enhancing cultivar quality.